2020
DOI: 10.14710/jitaa.45.4.356-364
|View full text |Cite
|
Sign up to set email alerts
|

A study on farmers’ choice in integrating paddy and cattle farming as farm management practices

Abstract: The study was conducted to examine the farmers’ choice on the technology of the paddy and cattle integration farming and determine factors that affected the integrated adoption. Primary data were collected through personal interview from 198 respondents divided into three categories (‘no integration’, ‘partial integration’, and ‘full integration’) based on the farmer’s utilization of manure and crop residues at Magelang Regency, Central Java Province, Indonesia. Then, the data were analyzed by multinomial logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It indicated that farmers who have attended informal education would be better at estrus detection for their sheep. Farmers who attend more training will get more information and skills in the livestock business (Budisatria et al, 2019;Widarni et al, 2020a). The experience of raising sheep in this study did not affect the knowledge of sheep estrus detection level.…”
Section: Resultsmentioning
confidence: 70%
“…It indicated that farmers who have attended informal education would be better at estrus detection for their sheep. Farmers who attend more training will get more information and skills in the livestock business (Budisatria et al, 2019;Widarni et al, 2020a). The experience of raising sheep in this study did not affect the knowledge of sheep estrus detection level.…”
Section: Resultsmentioning
confidence: 70%
“…Due to the lack of livestock groups, it is challenging to gather farmers, which creates a barrier to disseminating information about innovation transfer (Ibrahim et al 2021). However, farmers participating in training regularly obtain more knowledge and skills to adopt and implement sound management practices (Ngadiyono et al 2019;Widarni et al 2020).…”
Section: Beef Cattle Breeding Profilementioning
confidence: 99%
“…This creates an obstacle in the delivery of information related to good livestock management from the expert. Widarni et al [29] stated that farmers who attend training more frequently will get more information and skills needed to apply good management practices. Higher education and training can increase farmer awareness and readiness to adopt good farm management practices.…”
Section: Informal Educationmentioning
confidence: 99%